Digitalisation of education and cognitive load: Neurophysiological challenges for higher education institutions in the 21st century - Fazan, Vasyl; Fazan, Tetiana; Fazan, Vitaliy; Danylevskyi, Dmytro (Educational Challenges, 2025)
The purpose of the article is to analyse the impact of the digital transformation of education on the cognitive load of students of higher education institutions, taking into account neurophysiological factors. Methodology. The study used general scientific methods (analysis, synthesis, comparison, generalisation, systematisation) to study the scientific literature on the issue. The methodological basis is an interdisciplinary approach that combines pedagogical experience, neuropsychology, and cognitive ergonomics. The empirical part of the study contains the results of a survey of 50 students from V.G. Korolenko Poltava National Pedagogical University, Ukraine. We also used comparative analysis, structural methods and modelling of the integration of Cyber-Human Systems technologies into the educational process. Results. The analysis of the survey results shows that the vast majority of respondents consider the digital learning format to be a factor in increasing cognitive and psycho-emotional stress. This way, 80% of participants noted its increase compared to traditional forms, which correlates with the findings of neuropsychological studies on the negative impact of multichannel information delivery and high content dynamics on attention span and brain performance. At the same time, 76% of respondents acknowledged the positive impact of digital learning on the development of creativity and critical thinking, which is explained by the possibility of using interactive platforms, project work, and problem-based research tasks. The most effective strategies for reducing cognitive load are the use of interactive methods (41%) and a rational balance between work and rest (32%). Reducing the duration of classes (15%) and psychological support of teachers (12%) are considered as secondary, but no less important measures. Conclusions. We have found based on the theoretical analysis and empirical results of the study that the process of digitalisation of education in higher education institutions is accompanied by significant neurophysiological challenges associated with an increase in the cognitive load on higher education students. The identified trends make it possible to understand the need for a rational, systematic approach to determining the volume, structure, and pace of the educational material, taking into account the recommendations of modern cognitive psychology and neurophysiology. Only under the specified conditions it is possible to create an effective and safe educational space for students.